Early breast cancer in England: Evidence into practice: What can national cancer registration and analysis service datasets tell us?. (June 2019) - Smittenaar, R.; Bomb, M.; Rashbass, J.; Kipps, E.; Dodwell, D.
Highlights: NCRAS can provide rich data on the cancer patient pathway. Observational data can assess generalisability of RCTs and monitor adverse events. Equitable access to optimal treatments can be evaluated with observational data. Abstract: The English National Cancer Registration and Analysis Service (NCRAS) holds several datasets which provide detailed information on the cancer patient pathway. Ascertainment, data quality and completeness issues persist. However, there are still critical research questions that can be addressed using these data, which will help improve outcomes for patients. Registry data will help us understand whether the outcomes seen in highly selected patients in randomised controlled trials are realised at a national scale. These data can also help us monitor adverse events and toxicity profiles of drugs, helping clinicians make better prescribing decisions, as well as provide long term follow up for patients beyond the timescales of a trial. In instances where there is strong evidence for the efficacy of a treatment, such as the use of hormonal therapy in oestrogen positive breast cancers, observational data can help monitor and support adherence to these therapies. Finally, the wide variation in care provided to patients, including evidence of inequalities linked to socio-economic status is a public health concern. This can be quantified through population level observational data to facilitate measures to improve care.